Berbagai Inovasi Media Pembelajaran untuk Meningkatkan Minat Belajar Siswa - Naylla Ramadhani Gumbira; Desty Endrawati Subroto; Annisa Nurul Ulya; Ecih Sunensih; Marlina Nuraeni (Politeknik Kampar, 2025)
The rapid advancement of technology has become a crucial tool for achieving educational objectives more effectively and efficiently. However, it also presents a significant challenge for lecturers or teachers to enhance their skills in mastering technology and learning media. The role of learning media in the teaching and learning process is essential, as it serves as a tool to deliver messages from the sender to the recipient, while also helping students grasp the information shared by educators. Therefore, lecturers or teachers should incorporate media into the process. By doing so, using learning media can make the teaching and learning process more effective and efficient, while also fostering a stronger connection between teachers and students. Additionally, media can help alleviate boredom in the classroom. In summary, learning media is a method that addresses various challenges in teaching and provides students with comprehensive information.